A Literature Review and Case Report of Metastatic Pure Choriocarcinoma - Diwei Lin; Amanda Jia Hui Tan; Rajinder Singh-Rai (Case Reports in Oncological Medicine)
In 2012, testicular cancer was estimated to account for 940 disability adjusted life years in Australia; of these, 450 were years lost due to premature death and 500 were years of healthy life lost due to disease, disability, or injury (Australian Institute of Health and Welfare and Australasian Association of Cancer Registries, 2012). Testicular choriocarcinoma is one of the rarest variants of testicular germ cell tumours, accounting for less than 1% of testicular germ cell tumours and only about 0.19% of all testicular tumours. Management involves radical orchidectomy and chemotherapy. Even then, prognosis is poor. This case report describes a 20-year-old male with pure testicular choriocarcinoma with pulmonary metastases which showed sustained and complete response to adjuvant chemotherapy consisting of bleomycin, etoposide, and cisplatin.